Isolasi dan Identifikasi Bakteri Endofit Penghasil Hormon IAA (Indole Acetic Acid) dari Akar Tanaman Mangrove Avicennia marina - Suci Ramadani Pohan; Kartika Manalu; Rizki Amelia Nasution (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2024)
This research aims to determine the genus and potential isolates of endophytic bacteria producing IAA hormone from the roots of mangrove plants in Tanjung Rejo village, Percut Sai Tuan subdistrict. The research methods used include isolating endophytic bacteria using the plant method in NA (Nutrient Agar) media then culturing them in NB (Nutrient Broth) media then adding L-tryptophan and incubating, then identification is carried out based on morphological characterization, gram staining and biochemistry. The results of the research showed that 13 isolates of endophytic bacteria were found that had the potential to produce IAA hormones ranging from 0.047-0.050 ppm which were identified as the genus Enterobacter, Pseudomonas, Bacillus, Azosprilium, Micrococcus. However, the isolates BEAM PA 2 of the genus Enterobacter and BPAM PE 6 of the genus Micrococcus had the highest value of 0.050 ppm. The conclusion from this research is that the endophytic bacteria obtained as a whole have the ability to produce the hormone IAA. Keywords: Endophytic Bacteria, IAA (Indole Acetic Acid), Mangrove Avicennia marina